Review Of Pmik Readiness In The Implementation Of Electronic Medical Records (Rme) At The Islamic Hospital "Siti Hajar" Mataram: A Qualitative Study: Tinjauan Kesiapan Pmik Dalam Penerapan Rekam Medis Elektronik (Rme) Di Rumah Sakit Islam “Siti Hajar” Mataram: Studi Kualitatif - Susilawati, Wulandari Dewi; Hasanah, Uswatun; Yanuarti, Jihan; Permana, Yan Reiza; Pertiwi, Aditiyani Nugraha; Susilo, Beny Binarto Budi; Halid, Musparlin (Procedia of Engineering and Life Science, 2024)
Medical recorder and health information (MRHI) in the implementation of electronic medical records (EMR) at the Islamic Hospital (IH) “Siti Hajar” of Mataram is still not ready to implement EMR because there is no budget for its implementation, facilities and infrastructure as well as inadequate human resources and supporting devices in the implementation of EMR which are still inadequate. The study aims to identify the 5M elements (man, money, material, machine and methods) related to MRHI readiness in implementing EMR. The type of research used a qualitative design with interviews, observation and documentation. The research informants were the head of the medical record unit, coordinator of the medical record unit, medical record officers and information technology officers. The results of research from the man element, namely officers have not received special training related to EMR. The element of money is that officers do not know the budget related to the implementation of electronic medical records. The element of machine is that the facilities, infrastructure and supporting devices (hardware and software) are still inadequate. The material element is that there has been no creation of special documents related to the implementation of electronic medical records. The methods element, namely standard operating procedures (SOPs) related to the implementation of EMR does not yet exist. It is necessary to invest in technology upgrades, improve staff training programs, strengthen data security measures, and develop a comprehensive change management plan.